2010
DOI: 10.1111/j.1533-2500.2010.00404.x
|View full text |Cite
|
Sign up to set email alerts
|

14. Coccygodynia

Abstract: Coccygodynia is painful condition localized in the region of the coccyx. In most cases a traumatic etiology is present. In the idiopathic form other causes such as infections and tumor have to be excluded. Coccygodynia can also be the result of pain referred from visceral structures due to conditions such as disorders of the rectum, the colon sigmoideum, and the urogenital system. In case of a traumatic etiology the diagnosis is made based on the typical medical history whereby the pain is provoked by prolonge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 19 publications
1
53
0
8
Order By: Relevance
“…This difference is highly significant. These obtained results were in agreement with (18), (19) they all found that Lateral deviation of the coccyx is increased steadily with age and always greater in male groups than female groups. However, (19), (20) found that In fourth age group(20-40 years) of European individuals the Lateral deviation of the coccyx in male is 15.7°± 12.1° , while in female is 14.1° ± 11°.…”
Section: Measurements Of Coccyxsupporting
confidence: 82%
“…This difference is highly significant. These obtained results were in agreement with (18), (19) they all found that Lateral deviation of the coccyx is increased steadily with age and always greater in male groups than female groups. However, (19), (20) found that In fourth age group(20-40 years) of European individuals the Lateral deviation of the coccyx in male is 15.7°± 12.1° , while in female is 14.1° ± 11°.…”
Section: Measurements Of Coccyxsupporting
confidence: 82%
“…Coccygectomy, or surgical extraction of the coccyx, has been recommended in cases of acute trauma, including unstable fractures or recalcitrant pain, when conservative management has been deemed unsuccessful or has not provided sufficient relief. 1,3,6,[13][14][15][16][17] In a retrospective analysis of 32 individuals treated by an orthopaedic spine surgeon over a 5-year period, Hodges et al 5 reported that 13% of the patients were treated with nonsteroidal anti-inflammatory drugs alone, 53% were treated with both nonsteroidal anti-inflammatory drugs and local injections, and 34% underwent coccygectomy. In their study, those who underwent coccygectomy had significantly greater pain scores and slightly greater Oswestry Disability Index scores pretreatment than those who were treated conservatively.…”
Section: T T Discussionmentioning
confidence: 99%
“…El cóccix es una estructura ósea compuesta por 4 segmentos, los cuales están unidos entre sí por articulaciones no móviles (sinartrosis) y al sacro por un disco intervertebral rudimentario que permite su movilidad en el plano sagital (30). Embriológicamente, es el remanente de la cola embrionaria, evidente en la mayoría de los mamíferos pero que en seres humanos regresa dejando una estructura ósea (cóccix), un músculo isquiococcígeo y el ligamento sacroespinoso como vestigio.…”
Section: Aspectos Específicos Del Sacro El Cóccix Y La Pelvis Relaciunclassified
“…Cuando se hace crónico aparecen espículas óseas, deformidad y dolor. El síntoma doloroso es transmitido por el plexo simpático pélvico, los ganglios prevertebrales y el plexo coccígeo propio (ganglio impar de Walther) (30,32). La percepción dolorosa desde la región perineal y sacro-coccígea se caracteriza por ser una sensación difusa irradiada a la porción inferior de la región lumbar por comunicaciones interfasciculares del plexo sacro dorsal.…”
Section: Aspectos Específicos Del Sacro El Cóccix Y La Pelvis Relaciunclassified